CUSTOMER ASSESSMENT METHOD AND DIMENSIONS OF SERVICE QUALITY TO INFLUENTIAL REVENUE GROWTH (Case studies in Industrial Services Company) - J.E. Sutanto (Jurnal Teknobisnis, 2012)
Quality of service is a very complex discussion due to intangible substance or. The study was focused on the service industry companies in several Indonesia big cities. While the sample of service industry ware selected base on directorate of Large and Medium Companies. The survey conduct base on consumer needs and consumer wants, each service provide should have ability to determine those things trough market research. On services management, the role of human resources is more prominent and more decisive due to “moment of truth” importance. Quality of services is determined by the quality of the internal management especially for contact personnel. Therefore, internal factors are very dominant compared to external factors, thus, in Services Company, promotion has become important and effective to define consumer satisfaction, because consumer may determine organization development as well. Gross domestic product in the service sector has significant growth until year 2010, so the role managers should have attention to the developments and new challenges, such as new discoveries in technology, changes in society, economic of scale, economic environment, and the presence of international trade.